2003
DOI: 10.1121/1.1631945
|View full text |Cite
|
Sign up to set email alerts
|

Representation of concurrent acoustic objects in primary auditory cortex

Abstract: Auditory scene analysis involves the simultaneous grouping and parsing of acoustic data into separate mental representations (i.e., objects). Over two experiments, we examined the sequence of neural processes underlying concurrent sound segregation by means of recording of human middle latency auditory evoked responses. Participants were presented with complex sounds comprising several harmonics, one of which could be mistuned such that it was not an integer multiple of the fundamental frequency. In both exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 29 publications
(18 reference statements)
4
39
0
Order By: Relevance
“…The latency of this effect (ϳ80 ms), in conjunction with the fundamental frequency of the complex sound (200 Hz), implies that frequency periodicity, on which concurrent sound segregation depends, is extracted quickly (i.e., within the first 16 cycles of the stimulus). This speedy registration of inharmonicity is consistent with findings from a recent study by Dyson and Alain (2004), who found an effect of mistuning on auditory evoked potentials as early as 30 ms after sound onset. Evidence from animal studies also suggests that frequency periodicity is already coded in the auditory nerve (Palmer, 1990;Cariani and Delgutte, 1996) and inferior colliculus (Sinex et al, 2002;Sinex et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The latency of this effect (ϳ80 ms), in conjunction with the fundamental frequency of the complex sound (200 Hz), implies that frequency periodicity, on which concurrent sound segregation depends, is extracted quickly (i.e., within the first 16 cycles of the stimulus). This speedy registration of inharmonicity is consistent with findings from a recent study by Dyson and Alain (2004), who found an effect of mistuning on auditory evoked potentials as early as 30 ms after sound onset. Evidence from animal studies also suggests that frequency periodicity is already coded in the auditory nerve (Palmer, 1990;Cariani and Delgutte, 1996) and inferior colliculus (Sinex et al, 2002;Sinex et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…Recently, Snyder and Alain (2005) found an age-related decline in concurrent vowel identification, which was paralleled by a decrease in neural activity associated with this task. This age difference in concurrent sound segregation may reflect deficits in periodicity coding in the ascending auditory pathways (Palmer, 1990;Cariani and Delgutte, 1996) and/or primary auditory cortex (Dyson and Alain, 2004) in the left, right, or both hemispheres. Using magnetoencephalography (MEG), Hiraumi et al (2005) found a right-hemisphere dominance in processing mistuned harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…Such automaticity points to relatively low levels of the auditory system, and indeed physical modelling of the generators of the auditory P1-N1-P2 complex indicates that these waves are best modelled by current sources in or near the primary auditory cortices (Picton et al, 1999;. More evidence for the involvement of primary auditory cortex in stream segregation comes from a study by Dyson and Alain (Dyson & Alain, 2004), who reported that the first reliable effect of mistuning harmonic stimuli was a modulation of the amplitude of the Pa peak of the middle latency auditory evoked response. There is good evidence from convergent sources that the Pa wave is generated in primary auditory cortex (LiegoisChauvel et al, 1991;McGee et al, 1992;Pantev et al, 1995;Scherg & Von Cramon, 1986), and the early latency of this response (about 32 ms) is consistent with the preattentive processing of acoustic cues to auditory stream segregation.…”
Section: Cortical Generators Of the Ornmentioning
confidence: 99%
“…Previous ERP studies regarding variations in harmonicity have focused on issues such as the location and time course of mistuning processing Alain et al, 2002), the interaction between mistuning and location cues in sound segregation (McDonald & Alain, 2005), and whether the detection of harmonicity can operate in the absence of attention (Alain & Izenberg, 2003;Dyson & Alain, 2004;Dyson et al, 2005b). The present experiment extends ideas of harmonic detection by considering the ERP consequences of repeating or changing harmonicity and its relation to pitch change, rather than examining specific values of harmonicity per se (for an examination of the specific effects of stimulus token, see Dyson & Alain, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In the latter case, the "buzz" represents all hart monically related partials, and the pure tone component represents the inharmonic partial. Therefore, the mistuned harmonic paradigm can be used to distinguish between cases of singular and multiple concurrent objects within an auditory scene, with the tuned stimulus representing one object and the mistuned stimulus representing two (Alain, Arnott, & Picton, 2001;Alain, Schuler, & McDonald, 2002;Dyson & Alain, 2004).…”
mentioning
confidence: 99%